Poly Aluminum Chloride (PAC) as Coagulant in Liquid Waste Treatment of Tofu - Riva Ismawati; Rina Rahayu; Rizqa Puspitarini; Ahmad Muhlisin; Alene Tawang (Walisongo Journal of Chemistry, 2022)
The tofu craftsmen have not processed the liquid waste produced and disposed of the liquid waste directly into the waters as a result, the water quality has decreased. Tofu liquid waste has BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), and TSS (Total Suspended Solid) exceeding the permitted quality standards. Treatment of tofu liquid waste needs to be done before being disposed of, one of which is by using coagulant. The purpose of this research is to know the value of BOD, COD, TSS, and pH of tofu liquid waste before and after the addition of PAC. The study was conducted by varying the concentration of PAC (10 mg/L, 30 mg/L, and 75 mg/L). The test results show that the tofu liquid waste has a BOD value of 3,890 mg/L, COD 9558.7 mg/L, TSS 2,905 mg/L, and a pH of 3.7. The use of PAC as a coagulant reduced the values of BOD, COD, TSS, and pH. PAC concentration of 75 mg/L can reduce BOD, COD, TSS, and pH values to 3,015 mg/L, 6,900 mg/L, 840 mg/L, and 3.59, respectively.